Faktor-Faktor yang Mempengaruhi Penerimaan Buruh Pengupas Bawang Merah (Allium cepa L.) (Studi Kasus: Pasar Sambu, Kecamatan Medan Kota) - Mardiyah Siregar; Gustami Harahap; Mitra Musika Lubis (Universitas Medan Area, 2022)
Shallots are one of the horticultural commodities that are included in the spice vegetables which are used as a complement to cooking spices to add flavor and enjoyment to cooking. Becoming an onion peeler is an alternative job for some housewives around the sambu market. This study aims to determine the factors that influence the job acceptance of onion peeler workers at Sambu Market, Medan Kota District. This research was determined purposively that is determined intentionally. In this study, the number of samples used was 45 shallot peeler workers in Pasar Sambu, Medan District, Pasar Sambu City. The results of the study of the factors that influence the acceptance of shallot peeler workers are working hours and work wages. The variable score of working hours and higher wages has a significant effect on increasing the acceptance of onion peeler workers at Sambu Market, Medan City District. Judging from the acceptance value of shallot peeler workers at Sambu Market, Medan City District, this average income per month reaches Rp. 1,411,111. It can be said that shallot peeler workers have low acceptance. The magnitude of the effect of work experience, working hours, and work wages on the acceptance of shallot peeler workers at Sambu Market, Medan City District, which was measured using R2 was 0.763. This means that the independent variables in this model are able to explain the dependent variable of 76.3%.